Clinical-epidemiological characterization of patients undergoing hemodialysis therapy: An integrative review (Research, Society and Development, 2021)
The present study aimed to analyze, through the literature, the scientific evidence that involves the clinical and epidemiological aspects of patients undergoing hemodialysis therapy. This is an integrative literature review, which asked the following question: What is the scientific evidence on the epidemiological clinical characterization of patients undergoing the hemodialysis process? A PICo strategy was set up in which, through descriptors and keywords, the PubMed databases of the National Library of Medicine were consulted; VHL (Virtual Health Library), and CINAHL (Cumulative Index to Nursing and Allied Health Literature). The studies available in their entirety, published between the years 2015 to 2020, in Portuguese, English and Spanish were used. Thirteen studies were included in this review. The thirteen studies presented the clinical and epidemiological characterization of these patients, prevailing: male gender, age 20-59 years, low education, low income, with underlying diseases hypertension and diabetes mellitus, the most frequent complaints associated with hemodialysis, were changes headache, cramps, nausea, vomiting, mental changes and changes in lifestyle. Therefore, it is expected to contribute to the achievement of a continuous verification of the epidemiology of these chronic kidney patients, aiming at the early detection of this pathology, as well as the appropriate therapeutic approaches to prevent the development of the disease, seeking to minimize the suffering of these patients, always focusing in the integral care of individuals and the reduction of unfavorable outcomes.